2019
DOI: 10.1111/ele.13252
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient stoichiometry shapes microbial coevolution

Abstract: Coevolution is a force contributing to the generation and maintenance of biodiversity. It is influenced by environmental conditions including the scarcity of essential resources, which can drive the evolution of defence and virulence traits. We conducted a long‐term chemostat experiment where the marine cyanobacterium Synechococcus was challenged with a lytic phage under nitrogen (N) or phosphorus (P) limitation. This manipulation of nutrient stoichiometry altered the stability of host–parasite interactions an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Impacts of changes from N to P limitation on the relationships between bacteria and hosts (and vice versa) are strong due to the short life cycles of bacteria. Host selection in the cyanobacterium Synechococcus is more discriminant under N than P limitation, leading to changes in the co‐evolution of microbial communities associated with hosts that depend on intermediate N:P ratios (Larsen, Wilhelm, & Lennon, ). Similarly, changes in key ecosystem processes indirectly involved in community species composition, such as the transfer of energy and elements through trophic levels and nutrient cycling, have been correlated with changes in organismic N:P ratios (Ågren, ; Arnold et al, ; Güsewell & Gessner, ; Güsewell & Verhoeven, ; Penuelas et al, ; Vanni, Flecker, Hood, & Headworth, ; Zhang, Bai, & Han, and references therein).…”
Section: Impacts Of Shifts In the N:p Ratios Of Human Inputs On Organmentioning
confidence: 99%
“…Impacts of changes from N to P limitation on the relationships between bacteria and hosts (and vice versa) are strong due to the short life cycles of bacteria. Host selection in the cyanobacterium Synechococcus is more discriminant under N than P limitation, leading to changes in the co‐evolution of microbial communities associated with hosts that depend on intermediate N:P ratios (Larsen, Wilhelm, & Lennon, ). Similarly, changes in key ecosystem processes indirectly involved in community species composition, such as the transfer of energy and elements through trophic levels and nutrient cycling, have been correlated with changes in organismic N:P ratios (Ågren, ; Arnold et al, ; Güsewell & Gessner, ; Güsewell & Verhoeven, ; Penuelas et al, ; Vanni, Flecker, Hood, & Headworth, ; Zhang, Bai, & Han, and references therein).…”
Section: Impacts Of Shifts In the N:p Ratios Of Human Inputs On Organmentioning
confidence: 99%
“…4). Similarly, previous studies have showed that resource stoichiometry and soil microorganisms have a close relationship, and soil C:N:P stoichiometry shapes microbial coevolution, which is important for the maintenance of microbial biodiversity (Castle et al 2016;Larsen et al 2019). Generally, the growth of plants and soil microbes are limited by N, and there is competition for resources between plant roots and soil microbes under nutrient-poor conditions (e.g., N-limited environment, Wang and Bakken 1997;Kuzyakov and Xu 2013).…”
Section: Discussionmentioning
confidence: 81%
“…Resource stoichiometry impacts the composition and function of microbial communities across a broad suite of environments (Cherif and Loreau, 2007;Hibbing et al, 2010;Larsen et al, 2019), but this has not yet been explored in the human gut. Both dietary fiber intake (Hamaker and Tuncil, 2014) and dietary N (Holmes et al, 2017) have clear effects on gut microbial community composition and function, suggesting that dietary C:element ratios play a role in shaping the microbiome and its effects on health.…”
Section: Microbiome Mediation Of Diet-health Linksmentioning
confidence: 99%